Anti-inflammatory IL-10 is upregulated in both hemispheres after experimental ischemic stroke: Hypertension blunts the response - Fouda, Abdelrahman Y (BioMed Central, 2013)
BACKGROUND: Exogenous administration of the anti-inflammatory cytokine, interleukin 10 (IL-10), is known to promote neuroprotection and mitigate neuroinflammation after ischemia. However, endogenous expression and localization of IL-10 and its receptor (IL-10R) in the post-ischemic brain are still to be elucidated. In this investigation we aimed at determining the temporospatial expression of IL-10 in the rat brain relative to its systemic levels after ischemic stroke. METHODS: Wistar rats were subjected to either permanent (pMCAO) or 3-h temporary (tMCAO) middle cerebral artery occlusion and euthanized at either 24 or 72 h. IL-10/IL-10R levels were quantified in ischemic and contralesional hemispheres and compared to shams using multiplex bead array and Western blotting, respectively. Localization of IL-10/IL-10R with markers for neurons, microglia, astrocytes & endothelial cells were examined using double labeling immunofluorescence. IL-10 was also quantified in the brain tissue of spontaneously hypertensive rats (SHRs) at 24 h after tMCAO. RESULTS: After both pMCAO and tMCAO in Wistars, IL-10 was significantly upregulated in both hemispheres by ≈ 50% at 24 h while IL-10R expression was significantly decreased only at 72 h in the ischemic hemisphere. IL-10 and IL-10R expression highly co-localized with viable neurons in the ischemic penumbra and contralesional hemisphere. In hypertensive rats, IL-10 showed no significant contralesional upregulation and declined significantly in the ischemic side at 24 h post-ischemia. CONCLUSION: Our data highlights the involvement of the ischemic and contralesional neurons in the endogenous anti-inflammatory response after ischemic stroke through increased production of IL-10. This increase in IL-10 is blunted in hypertensive animals and may contribute to worse outcomes.